Store performance evaluation: A case study on BPDB'S shikalbaha power plant local store - Banerjee, Ashim (BRAC University, 2014)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2013.